Strategi Bauran Pemasaran Dalam Meningkatkan Penjualan Jasa Talent Di PT. Orange Production Asia - Massa, Donita Ellyzabeth; Citrawati, Luh Putu; Asmarani, I Gusti Ayu Ratih (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Pariwisata Bali, 2025)
This study analyzes how PT. Orange Production Asia applies marketing mix strategies to boost talent service sales, following a decline in 2023 after experiencing growth in 2022. The drop in sales is believed to be caused by limited service innovation, minimal promotional efforts, and difficulties in finding talents with flexible schedules. The research focuses on the seven elements of the marketing mix (7P): product, price, place, promotion, people, process, and physical evidence. Using a descriptive qualitative method, data was collected through interviews with company leaders and managers, direct observation, and documentation. Additionally, SWOT analysis and the SWOT Matrix (SO, ST, WO, WT) were used to develop strategic alternatives based on the company’s strengths, weaknesses, opportunities, and threats. The findings show that the current marketing strategies—especially product quality and the use of social media—have been effective in improving sales. However, challenges such as fluctuating event demand and limited available talents remain. To strengthen competitiveness, the study recommends diversifying services and expanding promotional channels.